Hubungan Aktivitas Fisik dan Pola Makan dengan Kejadian Hipertensi pada Lansia di Kelurahan Selabatu Wilayah Kerja UPTD Puskesmas Selabatu Kota Sukabumi - Firdaus, Mohammad Rizki; Utami, Rima Novianti; Fajriah, Nisa (Jurnal Pengabdian Ilmu Kesehatan, 2026)
The incidence of hypertension among the elderly is one of the major health problems. Hypertension is one of the most common conditions in older adults and is a major risk factor for cardiovascular diseases. Physical activity and dietary patterns are two lifestyle factors that play an important role in controlling blood pressure. This study aims to analyze the relationship between physical activity and dietary patterns with the incidence of hypertension. The research method used was a quantitative approach with a cross-sectional design. The sample consisted of 198 respondents selected using a cluster random sampling technique. Data were collected using the International Physical Activity Questionnaire (IPAQ) and the Food Frequency Questionnaire (FFQ). Data analysis was performed using Somers’ d test. The results showed that there was a significant relationship between physical activity and dietary patterns with the incidence of hypertension, with a p-value of 0.000 (<0.05) and a Somers’ d value of -0.14 (weak correlation). The direction of the relationship was negative (inverse), indicating that lower levels of physical activity and poorer dietary patterns are associated with a higher incidence of hypertension.